ZUNNUN AL-MISHRI (RIWAYAT HIDUP DAN KONSEP MAâRIFAHNYA) - Bahdar, Bahdar (Hunafa: Jurnal Studia Islamika, 2006)
Islamic religion serves as a set of divine teachings revealed to humans to comprehend and to apply in their lives. However, it cannot be denied that in Islam, there had appeared a comprehension towards Islamic teachings focusing on inner religious experiences, sufism. In Islam, sufism had appeared in the early period of its history. Therefore, there had been some sufis throughout the history of sufism. Zunnun al-Mishr is one of sufis who is very populer amongst Muslim scholars. This article will elaborate Zunnun al-Mishrâs mystical teachings.Â Kata Kunci: Zunnun al-Mishri, sufi, tasawuf, maârifah